SYNTHESIS OF SILVER NANOPARTICLES USING BIOREDUCTOR OF KETAPANG LEAF EXTRACT (Terminalia catappa) - Andi Rusnaenah; Muhammad Zakir; Prastawa Budi (Hasanuddin University, 2017)
It had been done research about biosynthesis of nanoparticle silver (AgNPs) by using extract of ketapang leaf. The characterization result spectrum UV-Vis, XRD,PSA, TEM, dan FTIR show that increasing concentration AgNO3 increase wavelength (), the best concentration AgNO3 is 1 mM with SPR at  430-432 nm. The increasing temperature tend to decrease intensity of absorption, the best temperature of synthesis is 30oC with intensity absorption 3.492 show the obtained crystal of silver with average size distribution about 47.1 nm. Based on TEM measurement, size of obtained AgNPs is 36 nm with ball shape. The –OH group responsible in reduction of AgNO3 to become AgNPs.